International maritime transport : perspectives - McConville, J.; Morvillo, Alfonso; Leggate, Heather (London ; New York : Routledge, 2005)
This book presents an interdisciplinary approach from a wide range of internationally based experts. The book includes chapters on topics across the spectrum of integrated subjects supplemented with contemporary articles and papers. Topics covered include: ports as interfaces; logistics; manpower and skills; financial risk and opportunities; the regulatory framework. Each part contains an introduction which explains the context of the chapter within the book and the contemporary state of the art. The book is sure to be of great interest to students and academics working on maritime studies, as well as being extremely useful to professionals and policymakers in the maritime industry.
Raising world maritime standards / His Excellency William O'Neill.
Includes bibliographical references and index.
Keywords: Shipping